Intervensi Booklet Bermarkah terhadap Peningkatan Perilaku Pencegahan Leptospirosis pada Ibu Rumah Tangga - Nurmalytasari, Na'wa; Kasjono, Heru Subaris; Rois, Ibnu; Sugianto, Sugianto (Jurnal Epidemiologi Kesehatan Indonesia, 2025)
Leptospirosis remains a public health concern in Indonesia, including in Bantul Regency. Data from Sewon I Public Health Center (Puskesmas) indicate a high incidence of cases, particularly among housewives who are considered a high-risk group. Effective education is essential to improve leptospirosis prevention behavior. This study aimed to determine the effect of a marked booklet as an innovative health education medium on improving knowledge, attitudes, and preventive actions against leptospirosis among housewives. The study used a quasi-experimental design with a pre-test and post-test control group approach. A total of 60 respondents were divided into two groups, namely the experimental group, which received education using the marked booklet, and the control group, which received education through lectures. Instruments used included questionnaires and checklists. The results showed no significant differences in baseline characteristics between the two groups (p > 0.05). After the intervention, the experimental group showed significant improvements in knowledge (100% in the good category), attitude (increased to 70% in the good category), and preventive action (100% in the good category), with p-values < 0.05. In conclusion, the marked booklet was effective in improving leptospirosis prevention behavior and is recommended as an effective educational medium. Keywords : Marked Booklet, Health Education, Leptospirosis Prevention